Boosting the Mechanical and Thermal Properties of CUG-1A Lunar Regolith Simulant by Spark Plasma Sintering - Yiwei Liu; Xian Zhang; Xiong Chen; Chao Wang; Yaolun Yu; Yi Jia; Wei Yao (Crystals)
The mechanical and thermal properties of the fabricated structures composed of lunar regolith are of great interest due to the urgent demand for in situ construction and manufacturing on the Moon for sustainable human habitation. This work demonstrates the great enhancement of the mechanical and thermal properties of CUG-1A lunar regolith simulant samples using spark plasma sintering (SPS). The morphology, chemical composition, structure, mechanical and thermal properties of the molten and SPSed samples were investigated. The sintering temperature significantly influenced the microstructure and macroscopic properties of these samples. The highest density (~99.7%), highest thermal conductivity (2.65 W·m−1·K−1 at 1073 K), and the best mechanical properties (compressive strength: 370.2 MPa, flexural strength: 81.4 MPa) were observed for the SPSed sample sintered at 1273 K. The enhanced thermal and mechanical properties of these lunar regolith simulant samples are attributed to the compact structure and the tight bonding between particles via homogenous glass.